Seleção De Caracteres Correlacionados Em Cubiu (Solatium Sessiliflorum Dunal) Empregando A Análise De Trilha - Silva Filho, Danilo Fernandes da; Anunciação Filho, Clodoaldo José da; Noda, Hiroshi; Reis, Odemar Vicente dos (Acta Amazonica, 1997)
Twenty nine accessions of Orinoco apple (S. sessiliflorum) from the germplasm collection of the Vegetable Breeding Program of the National Research Institute of Amazonia (ΓNPA) were evaluated in Northeastern Brazil. The trial was carried out in the Vitória de Santo Antão Experimental Station, of the Pernambuco State Research Enterprise (IPA), Pernambuco. A randomized complete block design, with four replications, was used. The following characters of agronomic importance were evaluated: stem diameter; plant height; leaf area; fruit width; fruit length; locule number; pulp thickness; total fruit number per plant; average fruit weight; total fruit yield; and total soluble solids (Brix). The genotypic correlations among characters were estimated and used in path coefficient analysis to determine their influence on yield. The greatest number of positive and significant correlations occurred with pulp thickness. Total fruit number per plant and pulp thickness were the characters with the greatest direct and positive influence on yield of cubiu.
Selection of Correlated Characters in Cubiu (Solatium sessiliflorum Dunal) Using Path Coefficient Analysis
Keywords: Solatium Sessiliflorum; Solanaceae; Association Among Characters; Plant Breeding; Path Coefficient Analysis; Solarium Sessiliflorum; Solanaceae; Associação Entre Caracteres; Melhoramento Genético; Análise De Trilha